Dampak Implementasi Kebijakan Otonomi Daerah Terhadap Peningkatan Kualitas Pelayanan Publik (Suatu Studi Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Halmahera Utara) - Lasa, Kristovel; Pangkey, Masje Silija; Kiyai, Burhanudin (Sam Ratulangi University, 2015)
Abstract : The research objective was to determine the impact of the implementation of the regionalautonomy policy towards improving the quality of public services in the Department of Population andCivil Registration Halmahera as Minister of State for Administrative Reform (MENPAN) No. 81/1993(Anonymous, 1993) confirms that the quality of service should be in accordance with joints as follows,simplicity, clarity and certainty, Procedures / Procedure for Public Services; Public Service requirements,both technical and Administrative; Giving Public Service; Security, Openness, Efficient, Economical,Justice Yang Evenly, and timeliness. To determine the indicator then, researchers used the method with amix of evaluative-descriptive quantitative-qualitative approach. The sample in this study consisted ofelements of employee / service personnel (n1) and the user community services (n2), each of 30 people.Given the nature of the sample is paired, then the fixed sample size of 30 people, where a sample ofemployees polled neighbor variable X, while samples of people asked their opinion of the variable Y.Based on the results of data analysis known that the hypothesis 1, which states that